ACRITARCHS AND CONODONTS FROM THE CAMBRO - ORDOVICIAN FURUHÄLL (KÖPINGSKLINT) SECTION (ÖLAND, SWEDEN) - GABRIELLA BAGNOLI (Rivista Italiana di Paleontologia e Stratigrafia, 2020)
Cambrian to Lower Ordovician acritarchs and Lower Ordovician conodont species have been recorded from the Furuhäll Section at Köpingsklint on Öland, Sweden. The acritarchs are represented by three different microfloras. The first is found at the base of the section investigated and is characterized by the association of Cristallinium cambriense with Eliasum llaniscum, Retisphaeridium dichamerum and R. howellii. This microflora has been recorded in strata previously referred to the Paradoxides paradoxissimus trilobite Superzone.